Tinjauan Desain dan Pengaruh Warna Tempat Sampah secara Psikologis serta Dampak yang Ditimbulkan terhadap Kehidupan Sosial Masyarakat dalam Konteks Lingkungan Hidup (Studi Kasus di Kota Bandung) - Aryani, Dewi Isma (Zenit, 2012)
Garbage problem is one of important issues in our country. In this modern era, garbage comes from industries and homes. Garbage can be recycled to produce biodegradable or ecofriendly fuel, fertilizer, alternative technology, even art and craft products. There are lots of ways to process garbage to be into converted precious products to meet human necessities. Referring to healthy environment, science and design have their contribution to solve and reduce the harmful effects coming from garbage. In this article, many kinds of garbage bins will be presented according to  their uniqueness, material, technology, function, colours or shapes as a design phenomenon.Keywords: garbage, design, environment, colour, concept